THE PROBLEM OF SPOILERS IN INTERNATIONAL NEGOTIATIONS (Вісник: Міжнародні відносини, 2025)
B a c k g r o u n d . International negotiations, particularly in the context of prolonged armed conflicts, are a complex process fraught with many impediments that can lead to failure. The search for a solution mutually acceptable to the conflicting parties can be hindered by the actions of spoilers aimed at disrupting peace talks or undermining agreements already reached. In this regard, the study of the problem of spoilers presents both scientific and practical significance. Methods. The following methods were employed in this study: system-structural, system-functional, problem-historical, and comparative analysis. Results. Steadman’s development of a theoretical model for spoilers, which categorizes them into three types (limited, greedy, and total), has sparked considerable academic discussion. The primary focus of researchhas been on understanding the causes and motives behind spoilers’ actions and the internal and external conditions that foster this phenomenon. In most scientific studies, the approach to researching the phenomenon of spoilers was based on the concept of negotiation, which usually considers negotiations as a process where two or more parties decide how to share the benefits of joint actions while the balance of costs and benefits determines the result of the interactions. At a particular stage, the price becomes too high, and the party(ies) may begin to act as spoilers. From this perspective, the most critical factor is the expected utility of maintaining the confrontation. In this broader framework, the spoilers are typically seen as actors who, for some reason,oppose a peaceful settlement, do not support it, or are sceptical about its results, to the point that some argue every negotiator can be a potential spoiler. In our opinion, conscious and deliberate actions aimed at undermining negotiations give grounds to classify an actor as a spoiler. Conclusions. Despite varying approaches to categorizing spoilers, scientists recognize that the emergence of this phenomenon is driven by a combination of objective and subjective interconnected reasons concentrated at local, regional and global levels. Further in-depth research is required to develop effective strategies for countering spoilers in each case through coordinated efforts from both the peace process participants and the international community
Keywords: spoiler, international negotiations, peace process, conflict